Practice of Infopreneurship by Librarians in Public University Libraries in South-South Nigeria - Friday, Jerry Eyerinmene; Sawyer-George, Oyinkepreye (Evidence Based Library and Information Practice, 2023)
Objective – The aim of this study was to examine the practice of infopreneurship by librarians in public university libraries in South-South Nigeria. The study specifically intended to identify purposes of engaging in infopreneurship, methods of running infopreneurship, forms of infopreneurship practiced, benefits derived from practicing infopreneurship, and challenges encountered in practicing infopreneurship by the librarians.Methods – The population of the study comprised all 175 librarians in 13 public university libraries in South-South Nigeria, which were purposively chosen for the study. The study employed convenience sampling to engage 102 librarians in the university libraries, who were involved in one form of infopreneurship or another. The librarians were identified through preliminary investigation, observation, and interaction with the librarians by the researchers. The instrument for data collection was a self-designed online questionnaire titled, “Librarians’ Infopreneurship Practice Questionnaire (LIPQ).” The instrument was validated by two experts in the Department of Library and Information Science in Niger Delta University, Bayelsa State, Nigeria. Reliability test was not conducted on the instrument, based on the knowledge that a valid test tends to be reliable. The researchers distributed 128 digital copies of the draft of the validated questionnaire to the librarians through personal WhatsApp accounts of the librarians, WhatsApp groups of the various university libraries and WhatsApp groups of the different state chapters of the Nigerian Library Association to which the librarians belonged. Out of the 128 questionnaires administered, 102 were properly completed by the librarians and returned, producing a response rate of 97.69%. The data collected were analyzed using weighted mean and standard deviation.Results – The results from data analysis revealed that the librarians’ purposes of engaging in infopreneurship were to earn extra income, provide for post-retirement, meet unforeseen demands, and develop themselves. The librarians’ methods of running infopreneurship were leveraging, customizing, facilitating access to, and providing instant delivery of information. They used the following forms of infopreneurship: information brokerage, reprographic services, research-aid services, book vending and internet services. Finally, challenges faced by the librarians in practicing infopreneurship were lack of adequate finance, business infrastructure, technical skill, and high rate of presence of non-professional infopreneurs.Conclusion – The findings in this study demonstrate that librarians under study practice infopreneurship primarily for purposes of making money and self-sustenance. They achieve this by leveraging, customizing, facilitating access to and providing quick delivery of information. With these methods, the librarians engage in information brokerage, reprographic services, internet services, research-aid services and book vending. In return, these information professionals enjoy additional income, financial independence, accumulated knowledge, and enhanced sense of fulfillment. However, the practice of infopreneurship by the librarians is hindered by shortage of sufficient funds, technical know-how, business facilities and high rate of presence of unprofessional infopreneurs in the business.